Cholangiography: true gallbladder duplication - García, Alan; Lavega , Alvaro; Soumastre, Alejandro; González, Rosana; González, Fernando (Cirugía del Uruguay, 2023)
An anatomical variant of the extrahepatic bile duct is presented, as is true gallbladder duplication. Congenital gallbladder malformations are categorized into positional and morphologic abnormalities, gallbladder duplication being included in the latter. The accepted classification is Boyden's. Based on the relationship of the cystic duct with the vesicular body, he described the “vesica fellea divisa” (bilobed vesicle that drains into a single cystic duct and shares a common embryological origin) and “vesica fellea duplex” (true vesicular duplication, two separate vesicles with vesicular ducts). independent cystics, double embryological origin).